2011
DOI: 10.1111/j.1095-8312.2011.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and taxonomic status of the Palearctic population of the stem borer Sesamia nonagrioides (Lefèbvre) (Lepidoptera: Noctuidae)

Abstract: The major pest of maize in Mediterranean Europe, the stem borer Sesamia nonagrioides (Lefèbvre) (Lepidoptera: Noctuidae), has a fragmented distribution, north and south of the Sahara. The present study aimed: (1) to clarify the uncertain taxonomic status of the Palearctic and sub-Saharan populations which were first considered as different species and later on as subspecies (Sesamia nonagrioides nonagrioides and Sesamia nonagrioides botanephaga) and (2) to investigate the origin of the Palearctic population wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…The parasitism success of C. typhae in European host populations, assessed in the present work, was initially questioned because European S. nonagrioides are genetically well differentiated from African populations (Moyal et al 2011), and they may have evolved immune responses adapted to European parasitoids and pathogens. However, the variation of reproductive success of C. typhae in the different host populations did not depend on the continental origin of the host, because C. typhae performed globally better in the Italian population than in the French and the Kenyan ones.…”
Section: Discussionmentioning
confidence: 99%
“…The parasitism success of C. typhae in European host populations, assessed in the present work, was initially questioned because European S. nonagrioides are genetically well differentiated from African populations (Moyal et al 2011), and they may have evolved immune responses adapted to European parasitoids and pathogens. However, the variation of reproductive success of C. typhae in the different host populations did not depend on the continental origin of the host, because C. typhae performed globally better in the Italian population than in the French and the Kenyan ones.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Europe, many studies have shown how the persistence of populations in separate glacial refugia (e.g., the Iberian, Italian, and Balkan peninsulas, the Caucasus region, North Africa, and microrefugia in the Alps) during the Quaternary climatic oscillations promoted genetic diversity in contemporary populations (Andersen, Havill, Caccone, & Elkinton, ; Habel, Lens, Rodder, & Schmitt, ; Huck, Buedel, & Schmitt, ; Niedzialkowska et al, ; von Reumont, Struwe, Schwarzer, & Misof, ; Rofes et al, ; Schmitt, ; Schmitt & Müller, ; Sim, Hall, Jex, Hegel, & Coltman, ; Stolting et al, ; Torroni et al, ). For outbreaking species, reconstructing the biogeographical history of the species can help to determine the factors that might be promoting their outbreak (e.g., Moyal et al, ; Song et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis separated the sequences into a network of closely related haplotype groups (with connected branches with less than 95% probability). Population diversity indices including haplotype diversity (h), nucleotide diversity (π) (Nei & Miller 1990) and F st for each population of S. nonagrioides were calculated using Arlequin 3.5.1.2 (Excoffier & Lischer 2010). The results of analyses of molecular variation (AMOVA) were visualized using a script of R statistic program integrated in the Arlequin.…”
Section: Phylogeography Of Sesamia Nonagrioides (Lepidoptera) In Iranmentioning
confidence: 99%